The doman method to develop vocabulary for learners with dyslexia in escuela de educación básica Educa. - Lavayen González, Marco Antonio (2023)
The main objective of this research is to demonstrate how the Doman method develops vocabulary for learners with dyslexia. This project was realized in Escuela de Educación Básica EDUCA, focusing on English teachers. Thanks to the review of previous studies, it is determined that for the application of the Doman Method, capacity, aptitude, age, knowledge, and neurological process, the active participation of the student, the time, the content, and the attractive and good quality materials are of utmost importance. The research is of qualitative paradigm under a descriptive participatory action research design. The instruments applied for the collection of the information were the teacher interview. The results obtained were contrasted with the theoretical bases previously reviewed. With the development of the research, it was possible to know through interviews with English teachers that the Doman method is not only applied to students with dyslexia since it also promotes inclusion in the classroom.